Environmental controls on soil organic carbon and nitrogen stocks in the high‐altitude arid western Qinghai‐Tibetan Plateau permafrost region. Issue 1 (16th January 2016) - Wu, Xiaodong; Zhao, Lin; Fang, Hongbing; Zhao, Yuguo; Smoak, Joseph M.; Pang, Qiangqiang; Ding, Yongjian
Abstract: While permafrost in the circum‐Artic has great influence on soil organic carbon (SOC) and total nitrogen (TN) stocks, this might not be the case in low‐latitude arid permafrost regions. We test this hypothesis in the western Qinghai‐Tibetan Plateau (QTP) permafrost region. Fifty‐nine soil profiles were analyzed to examine the SOC and TN distribution and the controlling factors in western QTP, which is a desert steppe ecoregion. Mean stocks of SOC (5.29 kg m −2 ) and TN (0.56 kg m −2 ) for the top 200 cm in this area were lower than those of the east QTP and circum‐Arctic regions. The SOC and TN stocks under vegetative cover with permafrost conditions were significantly higher than those of desert conditions. The SOC and TN stocks for the layers of different depths were related to the content of clay, silt, and moisture. Although the active layer thickness (ALT) had a significant negative correlation to soil moisture, the ALT explained little or no variance in the SOC and TN stocks. The results showed that in the vast permafrost regions of the western QTP, the SOC and TN stocks are very low, and the main controlling factors for the SOC and TN are soil texture, moisture, and vegetation type. The SOC pool in this area may not be as vulnerable to degradation associated with climate warming and thus not emit greenhouse gases at the same rate as other permafrost regions. The different response of the SOC in this region should be considered in carbon cycling models. Key Points: The soil organic carbon and total nitrogen stocks are low in western part of Tibetan Plateau The permafrost is not the controlling factor for soil organic carbon in arid area